2018
DOI: 10.1007/s11427-018-9391-7
|View full text |Cite
|
Sign up to set email alerts
|

Targeting histones for degradation in cancer cells as a novel strategy in cancer treatment

Abstract: The anticancer therapies with the joint treatment of a histone deacetylase (HDAC) inhibitor and a DNA-damaging approach are actively under clinical investigations, but the underlying mechanism is unclear. Histone homeostasis is critical to genome stability, transcriptional accuracy, DNA repair process, senescence, and survival. We have previously demonstrated that the HDAC inhibitor, trichostatin A (TSA), could promote the degradation of the core histones induced by γ-radiation or the DNAalkylating agent methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Therefore, in the case of prostate cancer, and potentially other cancer types, activation of SIRT1, rather than inhibition, will be beneficial as an anti‐cancer treatment. Such studies provide evidence for the therapeutic potential of compounds, which enhance HDAC activity (such as resveratrol) [ 111 ], in combination with other chromatin‐remodeling compounds that increase H2A.Z degradation by the proteasome, in cancer.…”
Section: Histone Degradation Under Perturbed Cellular and Systemic St...mentioning
confidence: 99%
“…Therefore, in the case of prostate cancer, and potentially other cancer types, activation of SIRT1, rather than inhibition, will be beneficial as an anti‐cancer treatment. Such studies provide evidence for the therapeutic potential of compounds, which enhance HDAC activity (such as resveratrol) [ 111 ], in combination with other chromatin‐remodeling compounds that increase H2A.Z degradation by the proteasome, in cancer.…”
Section: Histone Degradation Under Perturbed Cellular and Systemic St...mentioning
confidence: 99%
“…Histones serve a key part in cancer development and are expected to be a novel strategy in cancer treatment 28 . It has been reported that histone deacetylase 4 (HDAC4) is highly expressed in osteosarcoma, 29 which can be involved in the development of osteosarcoma by regulating cellular behavior.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Our research data revealed that miR-591 was downregulated in OS, consistent with the results reported by Luo et al 27 It was also the first demonstration that overexpression of miR-591 could impede OS Histones serve a key part in cancer development and are expected to be a novel strategy in cancer treatment. 28 It has been reported that histone deacetylase 4 (HDAC4) is highly expressed in osteosarcoma, 29 which can be involved in the development of osteosarcoma by regulating cellular behavior. For example, HDAC4 inhibition by miR-140 inhibited OS proliferation, apoptosis and invasion, 17 while long noncoding RNA MALAT1 modulates HDAC4 through binding to miR-140-5p, thereby promoting HOS and 143B cell growth.…”
Section: Discussionmentioning
confidence: 99%